Prenylated Xanthones from Calophyllum biflorum Leaves: Isolation, Structural Characterization, and Evaluation of Antioxidant and Cytotoxic Activities - Fitri Nurvita Sari; Harum Margasari; Leny Nur Fitriani; Novian Ilham Ramadhan; Muhammad Ulul ‘Azmi; Mulyadi Tanjung; Tjitjik Srie Tjahjandarie; Ratih Dewi Saputri (Journal of Multidisciplinary Applied Natural Science, 2026)
The Calophyllum genus, part of the Calophyllaceae family, produces xanthones as dominant secondary metabolites. Calophyllum biflorum M.R. Hend. & Wyatt-Sm. is an endemic plant of Kalimantan; however, the potential of its xanthone content and biological activity has never been explored. In this study, three known prenylated xanthones: gartanin (1), ananixanthone (2), and α-mangostin (3), were isolated from C. biflorum leaves. Their chemical structures were determined by HRMS and 1D/2D NMR. The antioxidant activities of xanthones 1–3 (via DPPH radical) and their cytotoxicity toward 4T1 breast cancer cells were assessed. Xanthones 1–2 showed strong DPPH activity (IC50: 4.40 and 34.34 µM, respectively). Gartanin (1) also exhibited moderate activity against 4T1 cells (IC50 =16.70 µM). These results indicate the prenylated xanthones from C. biflorum as antioxidant agents.